A Solution‐Processable Electron Acceptor Based on Dibenzosilole and Diketopyrrolopyrrole for Organic Solar Cells. Issue 6 (5th March 2013) - Lin, Yuze; Li, Yongfang; Zhan, Xiaowei
<x xml:space="preserve">Abstract</x> A novel linear non‐fullerene acceptor (DBS‐2DPP) based on dibenzosilole and diketopyrrolopyrrole is designed and synthesized. DBS‐2DPP exhibits strong and broad absorption and appropriate energy levels matching with P3HT. Solution‐processed BHJ OSCs based on P3HT:DBS‐2DPP show PCEs as high as 2.05%. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>